Analisis Fraud Diamond Dalam Mendeteksi Finansial Statement Fraud pada Perusahaan Manufaktur di BEI Tahun 2018-2020 - Muchriana Muchran; Asriani Hasan; Sri Nengsi Eka (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aimed to identify the potential for fraudulent financial statements using fraud diamond analysis. Fraud Diamond was a concept that explains the factors that lead someone to commit fraud, namely pressure, opportunity, rationalization and ability. The pressure factor was determined based on financial stability, external pressures and financial goals. The opportunity factor was determined based on the nature of the industry and effective monitoring. Rationalization was supported by rationalization. Finally, capability was proxied by using capability. This study used revenue management to identify the potential for fraudulent financial statements. Management was measured using the F-Score indicator. A targeted sampling method was used in the sample selection in this study, with the sampling criteria being the financial statements of manufacturing companies listed on the Indonesian Stock Exchange (IDX) in 2018-2020. Based on these criteria, a sample of 11 companies was obtained during the three-year financial reporting period. This study was conducted using quantitative methods. The results showed that the variables financial stability, external pressures, financial goals, and type of industry had a significantly positive effect in detecting the potential for fraudulent accounts. The effective monitoring variable had no positive and significant effect in detecting fraudulent deals. Meanwhile, rationalization and skills did not have a significant negative impact on detecting the potential for fraudulent financial reports.